2014
DOI: 10.1111/tct.12200
|View full text |Cite
|
Sign up to set email alerts
|

Top tips for a teaching fellowship

Abstract: Our aim for this article was to generate practical top tips for those doctors considering, about to start or having just commenced a dedicated teaching role, helping individuals to get the most from their time. It also explains what these teaching fellowships can involve, and gives those thinking of undertaking a dedicated teaching role a better idea of what to expect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
2
2
0
Order By: Relevance
“…In accordance with other studies, the CTFs were found to be using the opportunity to decide upon their future careers, 8,9,13 enhance their CV, 6,9,14 develop skills as an educator 8,9,14 and take some time for their lives outside of clinical practice. 6,7,13 Given that 43% of trainees are uncertain about their specialty choice after Foundation training, 15 pausing to consider career options is understandable.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In accordance with other studies, the CTFs were found to be using the opportunity to decide upon their future careers, 8,9,13 enhance their CV, 6,9,14 develop skills as an educator 8,9,14 and take some time for their lives outside of clinical practice. 6,7,13 Given that 43% of trainees are uncertain about their specialty choice after Foundation training, 15 pausing to consider career options is understandable.…”
Section: Discussionsupporting
confidence: 86%
“…In accordance with other studies, the CTFs were found to be using the opportunity to decide upon their future careers, 8,9,13 enhance their CV, 6,9,14 develop skills as an educator 8,9,14 and take some time for their lives outside of clinical practice. 6,7,13 Given that 43% of trainees are uncertain about their specialty choice after Foundation training, 15 pausing to consider career options is understandable. There also seems to be a growing acknowledgement, in this 16 that a wider portfolio of activities, including teaching, may be a way for doctors to sustain job satisfaction throughout their clinical career.…”
Section: Discussionsupporting
confidence: 86%
“…Another study suggests that CTFs can struggle with issues such as stigma towards the role from other clinicians, and a difficulty in resisting the pressure to fill gaps in clinical rotas . Fortunately, a recent article in Clinical Teacher is directed at new CTFs to advise them how to make the most of their time in post …”
Section: What Are Ctfs?mentioning
confidence: 99%
“…It is also possible to undertake qualitative or quantitative educational research dealing with pedagogic research or curriculum development or validating the role of new technologies in education13. Fellowships in medical education offer a range of opportunities to develop as an educator including delivery of teaching (undergraduate and postgraduate), development of simulation programmes, designing curriculae, assessment of learning and evaluation of the quality of education 12,14.…”
Section: Non-scientific Opportunitiesmentioning
confidence: 99%